Detection of Fungi in Acca Sellowiana (Berg) Burret Seeds Detecção de Fungos em Sementes de Acca sellowiana (Berg) Burret - Fantinel V.S.* (2017)
© 2017. All Rights Reserved.Acca sllowiana (Berg) Burret is a native fruit species in southern Brazil, which is attracting great interest due to the high economic potential of its fruit organoleptic potential; the main form of propagation of the species is sexual way. Aiming to determine the sanitary quality of seeds, three forms of detection of fungi were compared with and without surface sterilization. The seeds were derived from four counties in the state of Rio Grande do Sul and three counties in the state of Santa Catarina. The culture media of Potato Dextrose Agar (PDA), V8 (tomato juice) and the method of “Blotter Test” were tested. The following fungi were identified: Aspergillus niger, Aspergillus flavus, Penicillium sp., Colletotrichum gloeosporioides, Fusarium sp., Curvularia sp., Alternaria sp. Trichoderma sp. Epicoccum spp. and Phomopsis sp. The agarized media are more sensitive in the detection of fungi in Acca sellowiana seeds. The sterilization of seeds reduces the incidence of weed fungi.